Implementation of Competency-Based Performance Management System for Employees of PLTMG MPP Manokwari 2 - Selmi Dedi; Windhi Astuti; Luckhy Natalia Anastasya Lotte; Yulius Heri Saptomo (Return : Study of Management, Economic and Bussines, 2026)
Human resources are a major factor in determining organizational success. Competency-based performance management is essential as it connects employees' knowledge, skills, and attitudes to the achievement of strategic organizational goals. PLTMG MPP Manokwari 2, as an electricity provider in West Papua, faces significant human resource challenges, including employees working outside their fields of expertise, which impacts suboptimal performance achievement. This study aims to analyze the implementation of a competency-based performance management system for employees at PLTMG MPP Manokwari 2 in Manokwari Regency. The research employed a qualitative descriptive approach with data collected through observation, interviews, questionnaires, and documentation. Data analysis used the Miles & Huberman model (data reduction, data display, and conclusion drawing) and SWOT analysis to map strengths, weaknesses, opportunities, and threats. The findings indicate that performance planning, communication, and competency development have been applied relatively well, although competency measurement remains general and not detailed. SWOT analysis identified strengths in human resource quality and management support, weaknesses in competency indicators, opportunities from energy policy and technology, and threats from budget constraints and rigid work culture. The study concludes that competency-based performance management is being implemented but requires stronger indicators and more sustainable HR development programs.